Do positive relations with patients play a protective role for healthcare employees? Effects of patients' gratitude and support on nurses' burnout - Converso, Daniela; Loera, Barbara; Viotti, Sara; Martini, Mara (Frontiers in Psychology, 2015)
Background: A growing number of studies reveal that there are significant associations between a patient’s perception of quality of care and a health professional’s perceived quality of work life. Previous studies focused on the patients or on the workers. Alternatively, they centre the discussion on either the negative or the positive effects, both on patients and care workers. This research work focuses on the positive relationship with patients - a possible resource for care workers. Method: Study 1: a CFA was conducted to test the factorial structure and the tenure of the Italian version for patients of the Customer-initiated Support scale. Study 2: using a multi-group path analysis, the effects of work characteristics and of the relationship with patients on burnout were tested in two different contexts: emergency and oncology ward. Results: Study 1: the one-factor instrument shows good reliability, convergent and divergent validity. Study 2: for oncology nurses cognitive demands, job autonomy, and support from patients have direct effects on emotional exhaustion and job autonomy; interactions between cognitive demands and patients’ support have an effect on depersonalization. For emergency nurses cognitive demands and interactions between job autonomy and support from patients have effects on emotional exhaustion; job autonomy, patients support and gratitude have direct effects on personal accomplishment. Conclusions: Results confirm expectations about the role of patients’ support and gratitude in reducing nurses’ burnout, with differences in the two contexts: emergency nurses show higher burnout and lower perception of positive relationship with patients, but present more intense protective effects of the interaction between job autonomy and support/gratitude. Suggestions can be offered to managers in developing interventions to promote “healthy organization” culture that consider jointly employees and patients’ needs.